Gastro-oesophageal reflux in the irritable bowel syndrome. Issue 10 (October 1986) - Smart, H L; Nicholson, D A; Atkinson, M
Abstract : Symptomatic assessment and oesophageal investigations were done in 25 consecutive patients with the irritable bowel syndrome attending a gastroenterological clinic. Symptoms of gastro-oesophageal reflux, dysphagia, and a globus sensation were significantly commoner than in a control group of fracture clinic patients. Ambulatory oesophageal pH monitoring showed clearly abnormal reflux in 11 of 22 patients (50%). Nine patients had macroscopic endoscopic changes and a further 11 biopsy changes alone, of oesophagitis which was thus present in 80% overall. Lower oesophageal sphincter pressure was significantly less in irritable bowel patients than in age and sex matched controls, but upper oesophageal sphincter pressure was comparable in the two groups and disordered peristalsis was not found. Oesophageal symptoms in the irritable bowel syndrome are mainly caused by gastro-oesophageal reflux predisposed to by a subnormal lower oesophageal sphincter pressure, rather than by oesophageal spasm.